Endotracheal cuff pressure monitoring and regulation; continuous vs intermittent method: A prospective randomized trial / Mohammad Basyir Kasim - Mohammad Basyir, Kasim (2019)
Objectives: Evaluating the efficacy of TRACOE smart cuff manager which provides continuous regulation as an alternative to conventional intermittent endotracheal cuff pressure manometer usage in monitoring and maintaining desired pressure of 20 to 30 cm H20 in intubated ICU patients. Comparing the rate of complication in the form of ventilator associated pneumonia, length of ICU stay and mortality. Methods: This is a prospective randomized controlled trial (RCT), single-blinded (patient) involving adult patients intubated in intensive care unit of University of Malaya Medical Centre (UMMC), Kuala Lumpur. A total of 93 patients with minimum age of 18 years old were recruited. Patients were randomized into two groups – TRACOE and conventional method. Several parameters were evaluated – average endotracheal cuff pressure, total number and percentage of pressure outside the desired endotracheal cuff pressure. Complications which include ventilator associated pneumonia, length of ICU stay and rate of mortality were recorded. Results: TRACOE usage has better efficacy to conventional method in monitoring and maintaining endotracheal cuff pressure, however, it was not statistically significant. There is no difference in the rate of VAP or length of stay in both groups. Conclusion: The TRACOE smart cuff manager is as effective as the usage of conventional method in maintaining endotracheal cuff pressure and preventing the development of VAP.